Video game players show more precise multisensory temporal processing abilities - Donohue, S. E.; Woldorff, M. G.; Mitroff, S. R. (Attention, Perception, & Psychophysics, 2010)
Recent research has demonstrated enhanced visual attention and visual perception in individuals with extensive experience playing action video games. These benefits manifest in several realms, but much remains unknown about the ways in which video game experience alters perception and cognition. In the present study, we examined whether video game players` benefits generalize beyond vision to multisensory processing by presenting auditory and visual stimuli within a short temporal window to video game players and non-video game players. Participants performed two discrimination tasks, both of which revealed benefits for video game players: In a simultaneity judgment task, video game players were better able to distinguish whether simple visual and auditory stimuli occurred at the same moment or slightly offset in time, and in a temporal-order judgment task, they revealed an enhanced ability to determine the temporal sequence of multisensory stimuli. These results suggest that people with extensive experience playing video games display benefits that extend beyond the visual modality to also impact multisensory processing.